Ecología y potencialidades del subtrebol (II Reunión Ibérica de Pastos y Forrajes Badajoz, 1989)
Opportuníties for pasture improvement are important and will be decisives en the next future. Money coming from foreign aids should be destructive if arríving directly to farmers; it will be essentíal to improve the husbandry and grassland productivity, mainly by the best subclover strains and making also a good use of the local ones. The productivity coming from plant to animáis and farmers, will improve the country life and the culturalised science